CULTURAL IDENTITY, MORAL WISDOM, AND CREATIVE INNOVATION, INSIGHTS FROM MELANAU FOLKLORE - Hishamuddin, Siri; Hafizan, Mohamad Naim; Abdul Walid, Ali (2025)
Melanau folklore represents one of the most vibrant yet understudied repositories of indigenous knowledge in Sarawak. More than storytelling, these narratives function as vehicles of cultural identity, moral instruction, and ecological wisdom that guide community life. In the context of accelerating globalisation and the pressures of digital modernity, such traditions face increasing risk of dilution. This study examines the moral architecture embedded in Melanau oral literature and considers how these values may be revitalised across contemporary cultural, educational, and creative platforms. Drawing on a qualitative, interpretive approach, the research analyses twenty four folk narratives documented by Harold Stephen Morris in 1997. Through iterative close readings, inductive coding, and researcher triangulation, four interconnected moral domains were identified. These consist of Personal Development and Growth, Social and Cultural Values, Interactions with the Supernatural, and Environmental Stewardship. The domains illustrate how Melanau stories weave personal ethics, communal expectations, spiritual balance, and ecological responsibility into a cohesive moral worldview. The findings reveal that these stories cultivate resilience, emphasise respect for adet, encourage harmony between humans and spiritual forces, and embed ecological taboos that safeguard local environments. Together, they construct a cyclical ethical system in which the growth of the individual supports the stability of the community, legitimised by spiritual equilibrium and sustained by responsible interaction with nature. The study contributes to intangible cultural heritage discourse by offering a structured mapping of moral values within indigenous storytelling. It also highlights practical pathways for application, including curriculum enrichment, eco cultural tourism design, and creative industry innovation. By reframing Melanau folklore as both heritage and resource, the research argues for its continued relevance in strengthening cultural identity, fostering sustainability, and inspiring contemporary creative practices. This ensures that the wisdom held in these narratives remains actively interpreted and meaningfully lived by future generations.